Bibliometric analysis: Traditional games for character building - Satriawan, Rabwan; Bahri, Samsul; Irawan, Ewan; Firdaus, Firdaus; Nasrullah, Nasrullah (Universitas Tanjungpura, 2026)
Background. Games are a cultural heritage that has educational value and plays an important role in shaping the character of students, especially amid the dominance of digital games that tend to reduce social interaction and contextual learning experiences. Objectives. This study aims to analyse the development of trends in traditional game research in character building through a bibliometric approach that covers publication growth, author productivity, journal sources, institutional affiliations, country contributions, as well as topic network mapping and research opportunities. Methods. The method used was bibliometric analysis of 73 Scopus-indexed articles from 2002 to 2025 with the keywords ‘traditional games’ and ‘character’, which were analysed using VOSviewer, R Program, and Biblioshiny for network visualisation and trend mapping. Results. The results of the study show a significant increase in publications since the mid-2010s, with Indonesia as the main contributor in terms of the number of publications and citations. The theme of ‘traditional games’ has become the centre of a network connected to character education, early childhood education, social skills, and the integration of digital-based serious games, as well as showing a shift in focus from cultural aspects to pedagogical innovation and cultural literacy. Conclusion. It is concluded that traditional games have developed as multidimensional pedagogical instruments that support the cognitive, affective, and psychomotor domains of students, while also opening up opportunities for further research on technology integration, ethnomotor approaches, and the strengthening of implementative policies in the education system.